UJI KELAYAKAN MEDIA PEMBELAJARAN BERBASIS EDUCAPLAY PADA MATA PELAJARAN SKI KELAS VII - Muhammad Zaki Arrazin (JIP: Jurnal Ilmu Pendidikan, 2025)
This educaplay-based learning media feasibility test research aims to determine the feasibility of media and material. The problem obtained by researchers during the field is that the teacher who teaches SKI subjects in class VII is still using the lecture method so that it makes students feel bored, sleepy, and lack of enthusiasm for learning, therefore researchers are interested in bringing educaplay-based learning media so that students are not easily bored, sleepy, and their enthusiasm for learning increases because of the learning media presented. Based on the assessment technique with the Research and Development (R&D) method and Development (R&D) method using the V model. The research method used is research and development by following the procedures in the V model. The data collection technique used is a research instrument with quantitative data analysis. The feasibility results obtained from the feasibility test of educaplay-based learning media based on the aspects of media experts obtained 82% while based on the aspects of material experts obtained 98% with very feasible criteria for each aspect.